2019
DOI: 10.29252/j.health.10.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Hygiene and Related Oral Health Behaviors among Students Studying Science in Meshgin City

Abstract: Background & objectives: Governments and health related professionals have approved the importance of social determinants in many countries. Oral hygiene is one of the most important subjects which is attracted the attention of the individuals, families, government and health organization and policy makers. Decayed, Missing, and Filled Teeth (DMFT) indicator is one of the most epidemiologic indexes in dentistry indicating the situation of oral and dental health among people of a community. The present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In study by Mohamadkhah, tooth brushing, flossing, and use of mouthwash have been reported as 69 %, 34 %, and 69%, respectively [20]. Also, the study by Babaei indicated that 59.5% of students brush their teeth daily [21]. In the study by Halboub, the frequency of tooth brushing (less than twice per day) was reported as 24% [22].…”
Section: Discussionmentioning
confidence: 99%
“…In study by Mohamadkhah, tooth brushing, flossing, and use of mouthwash have been reported as 69 %, 34 %, and 69%, respectively [20]. Also, the study by Babaei indicated that 59.5% of students brush their teeth daily [21]. In the study by Halboub, the frequency of tooth brushing (less than twice per day) was reported as 24% [22].…”
Section: Discussionmentioning
confidence: 99%